How Social Media Enforces Athlete Accountability in Sport? - Novan Bastian Dwi Ardha; Kurnia Eka Sari; Ari Kamayanti (Universitas Majalengka, 2022)
This study aims to explore how social media enforces athlete accountability through a case study in badminton. This study employed netnography and supported by interpretive approach to understand accountability process in the social media, Twitter. The object of this study is a badminton fanbase account namely Badminton Talk. The finding indicated that this badminton fanbase account in Twitter brings a complete component of accountability into social media. The process of accountability was presented by spreading information regarding the misconduct of Indonesian badminton athletes, posting a clarification video from an athlete, evaluating the athlete’s explanation from the badminton fans, and followed by imposing sanctions for shortfalls in doing sport integrity. This study implies on enriching sport governance strategy to strengthening athlete accountability by using social media as it engages fans involvement.